Pemboikotan dalam Perspektif Hadis - Munir, Misbahul; Ahmad, La Ode Ismail; Sakka, Abdul Rahman; Fatmal, Abd Bashir; Amin, Muhammadiyah (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: This study aims to detail the issue of boycotting according to the review of hadith with a thematic approach in a research method that is a literary study (Library Research), namely examining the texts of the Prophet’s hadith. which explains the Prophet’s orders, actions or approval of the boycott action. Several results of this study indicate that the concept of boycott in the perspective of thematic hadith refers to the rejection of something with a specific intent and purpose, such as to weaken the economy, punishment/sanctions and threats. In the time of the Prophet. boycotts occurred in three areas: economics, politics and social fields. In detail, the forms of boycott actions are found in (1) stopping the supply of wheat to the people of Mecca, (2) blocking and confiscating the trade property of the infidel Quraysh, (3) besieging the Jews of Bani Nadhir and the people of Thaif, and (4) ostracizing three Companions of the Prophet who were absent from the Tabuk war.